PENGGUNAAN WHOLE BRAIN TEACHING (WBT) UNTUK MENINGKATKAN KEMAMPUAN BERBICARA MAHASISWA - Kusumayati, Lusiana Dewi (Widya Wacana: Jurnal Ilmiah, 2014)
This study was conducted to improve students' speaking skill. Most of the students found it difficult to speak even though they mastered many vocabularies and they were able to write correctly. Their difficulty occured because they were afraid of making mistakes. They were too shy to speak. Besides, lecturer's teaching  method was one of many factors causing this problem. In this study, the researcher used Whole Brain Teaching (WBT) to teach speaking for the students from the first semester of class 02 Slamet Riyadi University Surakarta academic year 2013/ 2014. Whole Brain Teaching is one of alternative method  which is effective to manage the class. The procedures of this method conducted based on Brain Based Learning. Brain learns something in five ways: seeing, saying, listening, doing, and feeling. When the lecturer teaches the classroom rules using Whole Brain Teaching, students' brain work maximally.  They see the symbols, listen the rules, say those rules, and make movement. When the teachers teach optimistically and entertaining, the students will have joyful feeling for having fun during teaching and learning process. The method used in this research was classroom action research. This study consists of 2 cycles; each cycle consists of three meetings. The procedures of this research is planning, acting, observing, and reflecting. The data gathered by using observation, field note, audio recording, and students' listening score. The development of students' speaking skill can be seen from the average of pre-test and post test score. The average of pre test score was 6.6. It became 7.3 in post test 1 and in post test 2 it became 7.8. based on this research, it can be concluded that Whole Brain Teaching can develop students' speaking skill. Hence, Whole Brain Teaching can be one alternative method for the lecturer to teach speaking.   Keyword: Speaking skill, Whole Brain Teaching, Action Research